2015
DOI: 10.18632/oncotarget.4479
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces triglycerides accumulation in prostate cancer cells and extracellular vesicles supporting growth and invasiveness following reoxygenation

Abstract: Hypoxia is an independent prognostic indicator of poor outcome in several malignancies. However, precise mechanism through which hypoxia promotes disease aggressiveness is still unclear. Here, we report that under hypoxia (1% O2), human prostate cancer (PCA) cells, and extracellular vesicles (EVs) released by these cells, are significantly enriched in triglycerides due to the activation of lipogenesis-related enzymes and signaling molecules. This is likely a survival response to hypoxic stress as accumulated l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
119
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 48 publications
4
119
0
Order By: Relevance
“…Lipids in cancer cells are the main fuel source for membrane synthesis and act as one of the major drivers in tumor cells, especially PCa, for growth and membrane synthesis [10]. Moreover, the rate of fatty acid synthesis and accumulation has been reported to accelerate in hypoxic PCa cells and tumor core as a survival response to hypoxic stress [11]. Following re-oxygenation, the accumulated lipids support growth and aggressiveness of PCa [8, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Lipids in cancer cells are the main fuel source for membrane synthesis and act as one of the major drivers in tumor cells, especially PCa, for growth and membrane synthesis [10]. Moreover, the rate of fatty acid synthesis and accumulation has been reported to accelerate in hypoxic PCa cells and tumor core as a survival response to hypoxic stress [11]. Following re-oxygenation, the accumulated lipids support growth and aggressiveness of PCa [8, 11].…”
Section: Introductionmentioning
confidence: 99%
“…24 In another study, we reported that hypoxic PCA exosomes are loaded with a significantly higher amount of triglycerides, and hypoxic PCA exosomes-induced invasiveness could be inhibited by celecoxib. 23 Furthermore, this study suggested the important role of lipids in the biogenesis of exosomes under both normoxic and hypoxic conditions. 23 In a recent review, Sceneay et al summarized the role of exosomes in the preparation of pre-metastatic niches and metastasis, suggesting that exosomes secreted by hypoxic cancer cells could have systemic effects and could promote cancer metastasis.…”
Section: Exosomes As Messenger Of Hypoxic Responsementioning
confidence: 63%
“…23 Furthermore, this study suggested the important role of lipids in the biogenesis of exosomes under both normoxic and hypoxic conditions. 23 In a recent review, Sceneay et al summarized the role of exosomes in the preparation of pre-metastatic niches and metastasis, suggesting that exosomes secreted by hypoxic cancer cells could have systemic effects and could promote cancer metastasis. 19 It is also suggested that by using the advanced mass spectrometry based proteomics analysis of tumor-derived exosomes, it is possible to estimate the oxygenation status of the patient’s tumors.…”
Section: Exosomes As Messenger Of Hypoxic Responsementioning
confidence: 63%
See 2 more Smart Citations